Local economies of Brexit. (May 2017) - North, Peter
Liverpool is a city which has, in many ways, undoubtedly and observably benefited from Objective One EU funding to the extent that there is pretty much universal agreement that this has underpinned the city's recent renaissance. That said, outside the city centre persistent long-term economic problems endure. This paper reviews the mixed experiences of Merseyside's Objective One 'Pathways to Inclusion' programme as an attempt to solve problems of concentrated deprivation, arguing that the success of conventional approaches has been mixed. Brexit provides an opportunity for a rupture with forms of local economic development that have been progressively neoliberalised through time. It argues for a focus on opportunities, not deficits and absences, using asset-based community development, diverse economies, and solidarity economy approaches.